Hepatitis C virus in hemophilia: Health‐related quality of life after successful treatment in the sixth Hemophilia in the Netherlands study - Cas J. Isfordink; Samantha C. Gouw; Erna C. vanBalen; Shermarke Hassan; Erik A. M. Beckers; Johanna G. van derBom; Michiel Coppens; Jeroen Eikenboom; Kathelijn Fischer; Louise Hooimeijer; Frank W. G. Leebeek; Frits R. Rosendaal; et al. (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Introduction Persons with hemophilia and hepatitis C virus (HCV) infection have a lower health‐related quality of life (HRQoL) than those never HCV infected. However, it is unknown whether HRQoL after HCV eradication is comparable to individuals never HCV infected. We aimed to compare HRQoL between HCV‐cured and never chronically HCV‐infected persons with hemophilia. Methods All persons with hemophilia in the Netherlands were invited for a nationwide study conducted in 2018–2019. For the current analysis, participants born before 1992 with data on HRQoL and HCV status were included. HCV status was collected from medical records. HRQoL was measured by RAND‐36 questionnaire, with a minimally important difference set at 4.0 points. Multivariable linear regression was used to adjust for age, hemophilia severity, HIV status, and self‐reported joint impairment. Results In total, 486 persons were eligible; 180 were HCV cured and 306 never chronically HCV infected. Compared with those never HCV infected, HCV‐cured individuals were older (57 vs. 53 years), more often had severe hemophilia (67% vs. 21%), and reported more impaired joints (median 3 vs. 0). Compared with those never HCV infected, adjusted RAND‐36 domain scores of HCV‐cured individuals cured were lower on all RAND‐36 domains except Pain, ranging from a difference of 4.5 (95% CI, −8.8 to −0.3) for Physical functioning to 11.3 (95% CI, −19.4 to −3.1) for Role limitations due to physical problems. Conclusion Despite effective HCV treatment, HRQoL of HCV‐cured persons with hemophilia is still lower than HRQoL of those never chronically HCV‐infected on all RAND‐36 domains. This implies that careful psychosocial follow‐up and support are indicated.